DEFORMATION OF WESTERN GREECE DURING NEOGENE CLOCKWISE ROTATION AND COLLISION WITH APULIA - van Hinsbergen D.J.J.; van der Meer D.G.; Zachariasse W.J.; Meulenkamp J.E. (My University, 2006)
Following an Early Miocene phase of N - S extension affecting the entire Hellenides, 50° clockwise rotation affected western Greece. Modern GPS analyses show rapid southwestward motion in southwestern Greece over subducting oceanic lithosphere and no motion in the northwest, where Greece collided with Apulia. We aim to identify the deformation history of western Greece associated with the rotation and the collision with Apulia. The timing of the various phases of deformation is constrained via detailed analysis of vertical motions based on paleobathymetry evolution of sedimentary sequences overlying the evolving structures. The results show that accompanying the onset of rotation, compression was re-established in western Greece in the early Langhian, around 15° Ma. Subsequently, western Greece collided with the Apulian platform, leading in the Late Miocene to a right-lateral strike-slip system running from the Aliakmon Fault Zone in northern Greece via the Kastaniotikos Fault and the Thesprotiko Shear Zone to the Kefallonia Fault Zone, offshore western Greece. NE-SW compression and uplift of the Ionian Islands was accompanied by NE-SW extension in southwestern Greece, associated with faster southwestward motion in the south than in the north. This led in the middle Pliocene (around 3.5 Ma) to collision without further shortening in northwestern Greece. From then onward, NW-SE to N-S extension east of Apulia, and gradually increasing influence of E-W extension in the south accommodated motion of the Hellenides around the Apulian platform. As a result, curved extensional basin systems evolved, including the Gulf of Amvrakikos-Sperchios Basin-Gulf of Evia system and the Gulf of Corinth-Saronic Gulf system. © Springer-Verlag 2005.
Keywords: AEGEAN; BIOSTRATIGRAPHY; NEOGENE; PALEOBATHYMETRY; VERTICAL MOTIONS; Cenozoic::Neogene; Кайнозой::Неоген